S1-bZIP Transcription Factors Play Important Roles in the Regulation of Fruit Quality and Stress Response - Wang, Hong; Zhang, Yunting; Norris, Ayla; Jiang, Cai-Zhong (Frontiers in Plant Science, 2022)
Sugar metabolism not only determines fruit sweetness and quality, but also acts as signaling molecules to substantially connect with other primary metabolic processes and, therefore, modulates plant growth and development, fruit ripening and stress response. The basic region/leucine zipper motif (bZIP) transcription factor family is ubiquitous in eukaryotes and plays a diverse array of biological functions in plants. Among the bZIP family members, the smallest bZIP subgroup, S1-bZIP, is a unique one, due to the conserved upstream open reading frames (uORFs) in the 5’leader region of their mRNA. The translated small peptides from these uORFs are suggested to mediate Sucrose-Induced Repression of Translation (SIRT), an important mechanism to maintain sucrose homeostasis in plants. Here, we review recent research on the evolution, sequence features, and biological functions of this bZIP subgroup. S1-bZIPs play important roles in fruit quality, abiotic and biotic stress responses, plant growth and development, and other metabolite biosynthesis by acting as signaling hubs through dimerization with the subgroup C-bZIPs and other cofactors like SnRK1 to coordinate the expression of downstream genes. Direction for further research and genetic engineering of S1-bZIPs in plants is suggested for the improvement of quality and safety traits of fruit.